Experimental and Theoretical Study of Two Salen Type Schiff Base Compounds as Corrosion Inhibitors on Mild Steel in 0.5 M H2SO4 Media - Sheikhshoaie, Iran; Baghaei, Fatemeh; Dadgarnezhad, Athareh (Asian Journal of Chemistry, 2010)
The effect of two synthesized salicylaldiminato Schiff base bis(2-hydroxy-3-methoxy)-1 ,6-diaminohexane salicylaldimine (A) and bis-(2-hydroxy)-1,6-diaminohexane salicylaldimine (B) compounds on the corrosion inhibition of mild steel in 0.5 M H2SO4 has been studied by using electrochemical Tafel polarization technique at 25°C. The results show that these compounds revealed a good corrosion inhibition in 0.5 M H2SO4 media. The inhibition efficiency changes with the type of Schiff base and the inhibition efficiency for compound A is higher than for compound B. The adsorption of compounds A and B on the mild steel surface in 0.5 M H2SO4 obeys the Langmuir isotherm. The correlation between the molecular structures and corrosion inhibition efficiencies of compounds A and B has also been investigated using AMI semiempirical calculations. The theoretical results have been compared with the experimental data and the relations between the inhibition efficiency and quantum parameters have been discussed. A good agreement between the inhibition efficiency of compounds A and B on mild steel in 0.5 M H2SO4 and theoretical data with some quantum chemical calculations on the structures of compounds A and B are found.